Methodology of Studies for Construction of Water Reservoir Dams in Countries Prone to Landslide Hazard - Igityan, Hayk; Elbakyan, Elbak; Hakobyan, Hayarpi; Petrosyan, Vanik; Karamyan, Raffi; Gevorgyan, Ani (Salehan Institute of Higher Education, 2025)
Construction of water reservoirs often has significant geomorphological and environmental impacts, particularly in regions prone to landslides. This study addresses the critical issue of slope stability in the context of the construction of a planned water reservoir in Astghadzor, Gegharkunik Marz, Armenia. The primary objectives are to investigate the stability of slopes, identify potential landslide triggers, and evaluate seismic impacts using advanced numerical modeling techniques. GeoStudio SLOPE/W software was employed, with calculations performed using the Morgenstern-Price and Spencer methods, which ensure rigorous equilibrium conditions for mountainous terrains. Field investigations and laboratory tests provided input data, forming an engineering-geology model for the analysis. The results reveal that the slopes remain stable under static loading conditions; however, seismic loading renders them unstable, particularly in soils related to Category III. Stability factors decrease by approximately 68% under adverse soil conditions. These findings underline the necessity for incorporating advanced stabilization measures and soil-specific interventions into the design of water reservoir dams. This study contributes to optimizing design methodologies, improving the safety of reservoirs, and guiding future research in landslide-prone and geologically challenging regions. Doi: 10.28991/CEJ-2025-011-01-016 Full Text: PDF